2020
DOI: 10.1155/2020/2753414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Bone/Bone Marrow Microenvironments on Prostate Cancer Cells and CD59 Expression

Abstract: Objective. To evaluate the effects of human bone marrow mesenchymal stem cells (hBMSCs) and osteoblasts (hFOB1.19) on PC3 prostate cancer cells. Methods. To simulate the in vivo interaction between the bone/bone marrow microenvironments and prostate cancer cells, we established cocultures of PC3 cells with hBMSC or hFOB1.19 cells and evaluated their effects on the proliferation, cell cycle distribution, cell migration, and invasion of PC3 cells. Quantitative reverse transcription polymerase chain reaction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…TRAF6, a major signal transducer in RANKL-activated OCG, essentially helps to activate some pivotal intracellular signaling pathways responsible for the regulation of osteoclast formation and function, namely, NF-κB and MAPKs (JNK, ERK, and p 38). , The NF-κB signaling pathway facilitates osteoclast formation, osteoclast function, and bone resorption after RANKL-to-RANK binding . An inactive form of NF-κB that is normally complexed with inhibitory protein IκBα is typically located in the cytoplasm during the resting state of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6, a major signal transducer in RANKL-activated OCG, essentially helps to activate some pivotal intracellular signaling pathways responsible for the regulation of osteoclast formation and function, namely, NF-κB and MAPKs (JNK, ERK, and p 38). , The NF-κB signaling pathway facilitates osteoclast formation, osteoclast function, and bone resorption after RANKL-to-RANK binding . An inactive form of NF-κB that is normally complexed with inhibitory protein IκBα is typically located in the cytoplasm during the resting state of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, a consistent set of 12 proteins associated with osteogenesis were identified across all samples, including ALB [ 35 ], ITGB1 [ 36 ], VIM [ 37 ], MSN [ 38 ], MYH10 [ 39 ], HADHA [ 40 ], GSS [ 41 ], COPG1 [ 42 ], SAMHD1 [ 43 ], DDX1 [ 44 ], PSMD9 [ 45 ], and MFGE8 [ 46 ]. Conversely, a subset of 10 proteins consistently implicated in osteoclastogenesis at both time points were identified, namely CDC37 [ 47 ], GNAT3 [ 48 ], PSAP [ 49 ], HMGB1 [ 50 ], CD59 [ 51 ], YBX3 [ 52 ] H3C1 [ 53 ], NLRP9 [ 54 ], CHMP5 [ 55 ], and DYNLL2 [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that these MSCs can alter the phenotype of PC3 cells and increase their expression of CD59 by activating the RANK/RANKL/OPG signaling pathway, which makes them less detectable by the immune system. However, since this was an in vitro model, it may not fully replicate the complex interactions between human BM‐MSCs, osteoblasts, and PCa cells (Yan et al, 2020). In rabbit models of BCa, the implanted BM‐MSCs can differentiate into vascular endothelial cells and stimulate angiogenesis in the tumor microenvironment, which may be the main pathway for promoting tumor growth (Zhang et al, 2010).…”
Section: The Beneficial Characteristics Of Mscsmentioning
confidence: 99%